Beyond Conventional: The New Horizon of Targeted Therapy for the Treatment of Advanced Non Small Cell Lung Cancer - Tartarone, Alfredo; Lapadula, Vittoria; Di Micco, Concetta; Rossi, Gemma; Ottanelli, Carlotta; Marini, Andrea; Giorgione, Roberta; Ferrari, Katia; Catalano, Martina; Voltolini, Luca; Mini, Enrico; Roviello, Giandomenico (Frontiers in Oncology, 2021)
In the last few years the advent of targeted therapies against oncogenic drivers significantly improved the survival of non small cell lung cancer (NSCLC) patients with a favourable toxicity profile. Therefore, genetic testing, including at least EGFR mutations and ALK/ROS1 rearrangements, should be performed in all NSCLC patients (in particular with adenocarcinoma) who received a diagnosis of advanced disease. This review focuses on novel druggable oncogenic drivers, such as MET exon 14 mutations/MET amplification, RET fusions, BRAF V600E mutations, KRAS G12C mutations, NTRK rearrangements, and HER2 alterations.